Consumer liking of steamed green Chinese cabbage (Brassica rapa ssp. chinensis) cultivated in formulated vegetable waste-based organic hydroponic solutions - Pardede, Erika; Siahaan, Ferlist; Hayati, Rita (Comunicata Scientiae, 2024)
Chinese cabbage or pak choy (Brassica rapa ssp. chinensis) is often consumed because of its high nutritional content and several health advantages. Due to their promotion as being healthier and more ecologically friendly, hydroponic vegetables have seen a recent spike in consumer interest. The production of Chinese cabbage involved the processing of the vegetable waste to create various hydroponic solution formulations (F1 = banana peels, eggshells, and bean sprouts; F2 = banana humps, onion peels, bean sprouts, and moringa leaves; F3 = moringa leaves, onion peels, and bean sprouts; and F4 = AB Mix solution). They were applied at concentrations of 600, 900, 1,200, and 1,500 parts per million. The aim of this study was to investigate the relationship between the type of hydroponic growth solutions and Chinese cabbage customer acceptance. As a result, using a hedonic test of consumer liking, a panel of 32 untrained individuals was asked to show their liking score on sensory attributes of Chinese cabbage. There was a significant difference in the color liking of Chinese cabbage as an effect of hydroponic solution formulation. However, both organic vegetable waste-based formulations did not statistically substantially affect consumer acceptance, which includes color, taste, flavor, texture, and overall liking. Ultimately, vegetable waste-based organic formulations can be used to produce Chinese cabbage that is as acceptable to customers as those prepared with inorganic AB-Mix solution.